Anatomical study of single incision contralateral C7 nerve transfer through subdural pathway - Yao, Long; Yan, Zhengcun; Wang, Xiaodong; Gu, Jiaxiang; Liu, Hongjun; Zhang, Hengzhu (Frontiers in Neuroanatomy, 2024)
Stroke is one of the main diseases that endanger patients' lives. It is an acute local, temporary, or persistent brain damage caused by cerebral tissue ischemia or bleeding, leading to various complications. Among them, limb hemiplegia caused by stroke can seriously affect the quality of life of patients. Therefore，how to restore the motor function of hemiplegic limbs is an urgent problem that needs to be solved, and it is also an important research topic at home and abroad. The contralateral C7 nerve transfer surgery for the treatment of spastic hemiplegia has been clinically applied for many years. Its initial surgical method was the anterior cervical subcutaneous pathway.However,with the advancement of technology and continuous improvement of surgical methods, the anterior esophageal posterior pathway and the modified posterior vertebral pathway are currently used, all of which are extraspinal pathways. This article proposes a surgical approach for the transfer of the contralateral C7 nerve through a single incision intraspinal subdural pathway through microanatomy and simulated surgery of the C7 nerve in the spinal canal, providing theoretical and clinical basis for the feasibility of contralateral C7 nerve transfer surgery in the spinal canal.